HER3 PET Imaging Predicts Response to Pan Receptor Tyrosine Kinase Inhibition Therapy in Gastric Cancer. - Esfahani, Shadi A.; de Aguiar Ferreira, Carolina; Rotile, Nicholas J.; Ataeinia, Bahar; Krishna, Shriya; Catalano, Onofrio A.; Caravan, Peter; Yen, Yi-Fen; Heidari, Pedram; Mahmood, Umar (Molecular Imaging & Biology, 2023)
Purpose: New generation of receptor tyrosine kinase inhibitors (RTKIs) have shown to improve survival in many solid tumors. However, an imaging biomarker is needed for patient selection and prediction of treatment response. This study evaluates the use of quantitative changes of HER3 on 68 Ga-NOTA-HER3P1 PET/MRI for prediction of early response to pan-RTKIs in gastric cancer (GCa).Procedures: GCa cell lines were evaluated for expression of RTKs, and downstream signaling pathways (AKT and MAPK). Cell viability was assessed following 24-72 h of treatment with 0.01-1 µmol/L of afatinib, a pan-RTKI. HER3-expressing afatinib-sensitive (NCI-N87) and resistant cells (SNU16) were selected for evaluation of changes in RTKs expression and downstream pathways, with 24-72 h of 0.1 µmol/L afatinib treatment. 68 Ga-NOTA-HER3P1 PET/MRI was performed in subcutaneous NCI-N87 and SNU16 xenografts (nu:nu, n = 12/group) at baseline and 4 days after afatinib treatment (10 mg/kg, PO, daily). Temporal changes in PET measures were correlated to HER3 expression in tumors, tumor growth rate, and treatment response.Results: With afatinib therapy, NCI-N87 cells showed increased total HER3 expression, and reduction of other RTKs and downstream nodes within 72 h, while SNU16 cells showed no significant change in total HER3 and downstream nodes. 68 Ga-HER3P1 PET/MRI showed increased uptake in NCI-N87 and no significant change in SNU16 tumors (day 4 vs. baseline SUVmean: 3.8 ± 0.7 vs. 1.6 ± 0.6, p < 0.05 in NCI-N87, and 1.5 ± 0.7 vs. 1.7 ± 0.7, p > 0.05 in SNU16). These findings were in concordance with HER3 expression in histopathological analyses and tumor growth over 3 weeks of treatment (mean tumor volume in treated vs. control: 11 ± 17 mm3 vs. 293 ± 79 mm3, p < 0.001 in NCI-N87, and 238 ± 91 mm3 vs. 282 ± 35 mm3, p > 0.05 in SNU16).Conclusions: Quantitative changes in HER3 PET could be used to predict response to pan-RTKI within few days after initiation of treatment and can help with personalizing GCa management.